Pathological characteristics of early to advanced gallbladder carcinoma and extrahepatic cholangiocarcinoma. (3rd March 2014) - Kijima, Hiroshi; Wu, Yunyan; Yosizawa, Tadashi; Suzuki, Takahiro; Tsugeno, Yuta; Haga, Toshihiro; Seino, Hiroko; Morohashi, Satoko; Hakamada, Kenichi
Abstract Biliary tract cancer (cancer of gallbladder and extrahepatic bile duct) is the most common malignancy of the biliary tract, and is considered to be a high‐grade malignancy. In this study, we reviewed 293 gallbladder cancers and 102 bile duct cancers for clarifying growth and invasion of the extrahepatic bile duct cancer. Only 10.5% (9/86) of the early gallbladder cancers showed lymphatic invasion, but neither venous invasion nor lymph node metastasis was noted in the early cancers. 70.6% (207/293) of the gallbladder cases were pT2‐3 cancers, and frequently showed lymphatic/venous/perineural invasion and/or lymph node metastasis. 12.7% (13/102) of the extrahepatic bile duct cancers were pTis or pT1 cancers, which were categorized as early cancers. Only 15.4% (2/13) of the early cancer showed vascular/perineural invasion and/or lymph node metastasis. The majority (87.3%) of the extrahepatic bile duct cases was pT2‐3 cancers, and frequently showed vascular/perineural invasion and/or lymph node metastasis. We also examined intramural invasion patterns; i.e. intramural invasion patterns were defined as infiltrative growth (IG) type, and destructive growth (DG) type. The overall survival rate of the gallbladder cancer patients with the DG type was significantly lower than that of the patients with the IG type, associated with frequent lymphatic/venous invasion and/or lymph node metastasis. Therefore, pathological characteristics are important for clinical manifestation of the gallbladder/extrahepatic bile duct cancers.